Ottoman foundation narratives :|context, genre, and generic instability - Dayanç, Mehmet Şamil. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This thesis focuses on the Ottoman foundation narratives, which were born as a prod uct of certain historicity and continue to exist today. Proceeding through three differ ent routes, this thesis, with an emphasis on context, questions the meaning of the ab sence of Ottoman foundation narratives on the one hand and seeks the conditions of possibility of its existence on the other hand. In the genre section, which comes after the context subtitle, which is claimed that the Ottoman founding narratives are a the matic subgenre, first of all, the relationship between literature and history is exam ined. Some claims about the foundational period of the Ottoman Empire as the sub ject of the discipline of history are presented, and then perspectives offered by genre theories and narratology are discussed. In this way, the focus is on the Ottoman foun dation narratives, which started in 1949/1950, were written one after the other in the second half of the 1960s, and continued to exist with some consensus after 1980. In the subtitle of generic instability, the repetitions mentioned in the genre section are underlined, and the route leading to difference is followed. The route that started with Osmanoğulları, deviated to a different route with Devlet Ana, gained its domi nant characteristics with Ovaya İnen Şahin, Osman Gazi, Turgut Alp, and Kutlu Dağ in the 1970s, and reached a consensus with Osmancık, will be discussed with the em phasis of difference and repetition. On the one hand, the meanings of repetitions that make the Ottoman foundation narratives thematic subgenres will be questioned; on the other hand, “literature as a socially symbolic act” will be underlined by focusing on oscillations by considering the route leading to difference.
Keywords: Turkish literature -- Narrative.